The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/mmce.21157
|View full text |Cite
|
Sign up to set email alerts
|

A decoupled source current reconstruction method for noisy and reactive near-field to far-field transformation

Abstract: In this article, a decoupled source current reconstruction method (SRM) for noisy and reactive near-field (NF) to far-field (FF) transformation is introduced. It is shown that the traditional SRM for NF/FF transformation shows instability in the regions that the amounts of noise or reactive radiations are noticeable. Therefore, in these regions, equivalent currents should be determined from a Tikhonov SRM equation. However, this equation increases the computational cost of the SRM. To simplify the Tikhonov SRM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…When PD occurs in HV equipment, the near-field to far-field transformation used for the study the signal propagation is based on Huygens' Principle (the equivalence theorem) [26][27][28]. The radiating sources of PD are enclosed inside surface S, as shown in Figure 1.…”
Section: Near-field To Far-field Transformation Methodsmentioning
confidence: 99%
“…When PD occurs in HV equipment, the near-field to far-field transformation used for the study the signal propagation is based on Huygens' Principle (the equivalence theorem) [26][27][28]. The radiating sources of PD are enclosed inside surface S, as shown in Figure 1.…”
Section: Near-field To Far-field Transformation Methodsmentioning
confidence: 99%
“…Source current reconstruction method (SRM) is an efficient technique for reconstructing equivalent currents of the antenna under test (AUT) from the near (NF) or far-field (FF) measurements [1][2][3][4][5][6][7][8][9][10][11]. This method is based on the equivalence principle in which the AUT radiation is modelled by the equivalent currents at a fictitious surface enclosing the original AUT sources.…”
Section: Introductionmentioning
confidence: 99%
“…In all of these papers, it has been shown that the Tikhonov SRM is more stable in the presence of Gaussian noise or systematic measurement errors. In a recently published paper by the authors, it is demonstrated that the Tikhonov SRM is also necessary for the noiseless region with a large amount of reactive radiation [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation